Impact of the Covid-19 Pandemic on Agroecological Family Farming in the Backlands Territory from Araripe in Pernambuco - Coriolano, Jose Washington Gomes; Oliveira , Lucia Marisy Souza Ribeiro de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The present reality of the Pandemic caused by the COVID-19, is characterized by new adaptations in the decrease of the social and economic activities, with the social isolations, in cities and countryside communities, causing a decrease in the commercialization of food by the familiar agriculture, damaging the activities of social organization and rural technical advice in the sustainable development of agricultural activities, by the non-governmental institutions and representative entities of the civil society, in the implementation of public policies assisted to the farmers, having a greater consequence in the social vulnerability and rural poverty. The present article aims to study the effects of the pandemic on family farming in the territory of the backlands from Araripe in the state of Pernambuco, describing the strategies adopted in the social organization of countryside communities, in reducing the social impacts of the pandemic on family farming. Through a bibliographical research, based on academic literature, newspapers and institutional reports, on the activities of rural technical assistance with principles of agro-ecology, developed during the period of incidences of the pandemic. As a result, technological strategies were identified in the remote media, for the activities of rural technical assistance, organization of marketing of food products from family farming, at home, in greengrocers and emporiums of solidary marketing, assisted by non-governmental institutions, in the development of motivational initiatives for rural families, in overcoming social and economic difficulties, during this phase of social isolation and safety protocols to the health of countryside area families and the entire world population.